2019
DOI: 10.1021/acs.est.9b02119
|View full text |Cite
|
Sign up to set email alerts
|

Hydrolysis of Chloramphenicol Catalyzed by Clay Minerals under Nonaqueous Conditions

Abstract: Soil contamination with antibiotics has raised great environmental concerns, while the abiotic degradation of antibiotics on drought soil particles has been largely ignored. In this study, we examined the transformation of chloramphenicol (CAP) on phyllosilicates under nonaqueous conditions. A significant hydrolysis of CAP mediated by kaolinite occurred under moderate relative humidities (RH: 33–76%) with the half-lives of 10–20 days. By contrast, incubation with montmorillonite did not result in detectable de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 58 publications
0
12
0
Order By: Relevance
“…As natural soil is usually not fully water-saturated (with water content from 2 to 60%), , the reactions of organic contaminants under limited moisture conditions might be completely different from those occurring in aqueous solution. ,, Prior studies demonstrated that the hydrolysis of organophosphorus pesticides catalyzed by phyllosilicates was highly moisture-dependent, and the reactions were greatly enhanced under dry conditions with water content <10%. Similarly, the low moisture also accelerated the hydrolysis of NO 2 and carbonyl sulfide and other compounds by surface hydroxyl groups on atmospheric mineral dusts. In addition, our recent research found that the drought-surface of kaolinite and montmorillonite significantly catalyzed the hydrolysis of chloramphenicol (CAP) antibiotic via forming surface hydrogen bonds or inducing surface Brønsted/Lewis acidities. , Further investigation showed that limited surface water could facilitate CAP to diffuse into the reactive sites on a clay surface, while excessive water molecules would compete for surface reactive sites. , …”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…As natural soil is usually not fully water-saturated (with water content from 2 to 60%), , the reactions of organic contaminants under limited moisture conditions might be completely different from those occurring in aqueous solution. ,, Prior studies demonstrated that the hydrolysis of organophosphorus pesticides catalyzed by phyllosilicates was highly moisture-dependent, and the reactions were greatly enhanced under dry conditions with water content <10%. Similarly, the low moisture also accelerated the hydrolysis of NO 2 and carbonyl sulfide and other compounds by surface hydroxyl groups on atmospheric mineral dusts. In addition, our recent research found that the drought-surface of kaolinite and montmorillonite significantly catalyzed the hydrolysis of chloramphenicol (CAP) antibiotic via forming surface hydrogen bonds or inducing surface Brønsted/Lewis acidities. , Further investigation showed that limited surface water could facilitate CAP to diffuse into the reactive sites on a clay surface, while excessive water molecules would compete for surface reactive sites. , …”
Section: Introductionmentioning
confidence: 94%
“…33−35 In addition, our recent research found that the drought-surface of kaolinite and montmorillonite significantly catalyzed the hydrolysis of chloramphenicol (CAP) antibiotic via forming surface hydrogen bonds or inducing surface Brønsted/Lewis acidities. 36,37 Further investigation showed that limited surface water could facilitate CAP to diffuse into the reactive sites on a clay surface, while excessive water molecules would compete for surface reactive sites. 36,37 In this study, we hypothesize that different iron minerals would impose different interaction modes to antibiotics with respect to surface moisture, thus inducing varied hydrolytic performance.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…PAEs are hydrolysable, however, at slow hydrolysis rates with the hydrolysis half-lives ( t 1/2 ) even up to several years under neutral pH conditions 9 . In our previous studies, we found that chloramphenicol antibiotic could be rapidly hydrolyzed by clay minerals and iron oxides under limited surface moisture conditions, attributing to the strong Brønsted-/Lewis-acidities of the dry mineral surface 10 12 . By contrast, under water-oversaturated conditions, the surface reactions were completely suppressed due to the shielding effect of surface water layers 10 12 .…”
Section: Introductionmentioning
confidence: 94%
“…In our previous studies, we found that chloramphenicol antibiotic could be rapidly hydrolyzed by clay minerals and iron oxides under limited surface moisture conditions, attributing to the strong Brønsted-/Lewis-acidities of the dry mineral surface 10 12 . By contrast, under water-oversaturated conditions, the surface reactions were completely suppressed due to the shielding effect of surface water layers 10 12 . Therefore, moisture plays an important role on surface-mediated reactions.…”
Section: Introductionmentioning
confidence: 94%